Author Correction: Conjugation of wildtype and hypoallergenic mugwort allergen Art v 1 to flagellin induces IL-10-DC and suppresses allergen-specific TH2-responses in vivo - Stefan Schülke (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.